Correlation of Placental Thickness with Gestational Age and Other Fetal Parameters Among Pregnant Women: A prospective cross-sectional study from North India (Journal of Pharmaceutical Negative Results, 2022)
Background: Placental thickness is the lone parameter that can predict gestational age without relying on the foetus. For many years, the last menstrual period (LMP) date has been used to calculate the foetus gestational age; but, as shown by the studies, approximately 56 percent of females can recall the last menstrual period date with absolute precision. This forgetting might not have a big impact on an uncomplicated pregnancy, but in complicated pregnancies, proper foetal gestational age data is vital. In order to determine the relationship between placental thickness and foetal age and other growth parameters, this study was carried out.Methods: Between July 22, 2021, and July 22, 2022, the Department of Anatomy at Santosh Medical College and Hospital in Ghaziabad, Uttar Pradesh, India, worked with the Departments of Radiology and Obstetrics & Gynaecology on this prospective cross-sectional study. The convenient sampling technique was used to enrol the study subjects, and during the first five months of study, 254 ANC subjects with gestational ages between 11 and 20 weeks were included in the study. The pregnant subjects were examined by USG machine for gestational age (GA), and placental thickness (PT). The analysed data were represented as frequency, percentages, mean, median standard deviation (SD), minimum and maximum values.Results: Among enrolled pregnant subjects, the most common placenta positions were anterior (42.6%) and posterior (30.1%). Between the time of enrolment in the study (1.61±0.26 cms), the first follow-up visit (2.62±0.07 cms), and the second follow-up visit (3.35±0.26 cms), the mean placental thickness significantly increased. A very significant association (r=0.746) was found between gestational age and placental thickness in the Pearson correlation analysis of subjects between 31 and 40 weeks of gestation. Similar to this, a very significant correlation (r=0.965) was found between gestational age and foetus gestational weight.Conclusion: In our study during the first, second, and third trimesters of pregnancy, there was a significant linear association between placental thickness, gestational age, and other foetal parameters. Statistics was found to support the relationship.